2017
DOI: 10.1061/(asce)su.1943-5428.0000205
|View full text |Cite
|
Sign up to set email alerts
|

Combination of GPS and Leveling Observations and Geoid Models Using Least-Squares Variance Component Estimation

Abstract: In the last few years, satellite-based positioning techniques, such as the Global Positioning System (GPS), proved their abilities in various geodetic fields. Height determination, as one of such applications, requires a more likely correct geoid model to provide reliable geoid heights for transformation of the ellipsoidal heights to orthometric heights. An important step is then to establish such a model by optimal combination of the available geoid models. This can be achieved via variance component estimati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(3 citation statements)
references
References 45 publications
0
3
0
Order By: Relevance
“…Fotopoulos (2005) applied various polynomial functions to adjustment of geoid models and showed that the type of functional model affects the estimated values of standard deviations [6]. Khazraei et al (2017) used the bi-linear and the bi-quadratic polynomials to approximate and analyze the accuracy of the geoid models in a small area (~100 km 2 ). The results prove that the bi-quadratic polynomial was the best model fitted in this study [7].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Fotopoulos (2005) applied various polynomial functions to adjustment of geoid models and showed that the type of functional model affects the estimated values of standard deviations [6]. Khazraei et al (2017) used the bi-linear and the bi-quadratic polynomials to approximate and analyze the accuracy of the geoid models in a small area (~100 km 2 ). The results prove that the bi-quadratic polynomial was the best model fitted in this study [7].…”
Section: Introductionmentioning
confidence: 99%
“…Khazraei et al (2017) used the bi-linear and the bi-quadratic polynomials to approximate and analyze the accuracy of the geoid models in a small area (~100 km 2 ). The results prove that the bi-quadratic polynomial was the best model fitted in this study [7]. Das et al (2017) developed the geoid surface using second, third and fourth degree polynomials [8].…”
Section: Introductionmentioning
confidence: 99%
“…Saadat et al [2018] determined the regional geoid model of Iran, IRG2016, based on the radial basis functions. Combination of regional and global geoid models, in a small-scale region in Iran, has been studied by Khazraei et al [2017]. They used LS-VCE to evaluate the EGM2008 and GGMplus Earth geopotential models and IRGeoid10 in terms of agreement to the GNSS/leveling observations.…”
Section: Introductionmentioning
confidence: 99%